The Legality of Digitalization of Marriage Dispensation in Religious Courts: A Legal Perspective: Legalitas Digitalisasi Dispensasi Pernikahan di Pengadilan Agama: Perspektif Hukum - Yuliana, Atik; Ishaq; Nurcahyono, Moh. Lutfi (Universitas Muhammadiyah Sidoarjo, 2024)
The implementation of the Marriage Law in Indonesia has led to a notable surge in Marriage Dispensation requests, particularly observed at the Bondowoso Religious Court. This study aims to investigate the efficacy of the Marriage Dispensation Integration System (SIDIKA) application at the Bondowoso Religious Court through empirical juridical research methods. Analyzing data from 2019 to 2022, a significant reduction in Marriage Dispensation requests post-SIDIKA implementation is evident, with cases dropping from 299 in 2019 to 718 in 2022. This suggests a successful utilization of SIDIKA in streamlining dispensation processes. The implications underscore the potential for digitalization to enhance efficiency and accessibility in legal procedures concerning marriage dispensation, offering insights for broader adoption in similar contexts globally. Highlights: The surge in Marriage Dispensation requests post-Marriage Law enactment. Drastic reduction in Dispensation requests following SIDIKA implementation. Implications of digitalization for legal procedures and court efficiency. Keywords: SIDIKA, Religious Court, Marriage Law